Assessing the Social Media User’s Credibility Rating of Shared Content, and its Utilization in Decision Making - Hadiza Wada (Emerging Science Journal, 2021)
This study seeks to ascertain the degree to which people rely on unprofessionally processed information from social media to make decisions or take critical actions. Professional media, in this case, refers to the traditional broadcast and print media who have been in the business of professionally processing and authenticating information for their audiences. While social media represent the various platforms for social exchange of information. Relevant to this study is the social media’s ability to reach multitudes of people with unsubstantiated information. The methodology employed is simple random sampling, using questionnaire as an instrument. 350 respondents provided input using three age ranges, 20-35, 36-50, and 50 and above. The results show social media usage as the only news source for the youngest age group at 38%. The 50 plus years mainly rely on professional media. While all three age groups admitted to sharing of unsubstantiated information at 68%, only 30% admit to using critical information from social media. Most importantly, the findings indicate; where prevalence and availability tends to overwhelm users, taking the time to seek more credible information takes a back seat, even in cases where the information sought is critical to decision making and use. Doi: 10.28991/esj-2021-01269 Full Text: PDF